Determination of the radiological risk from the natural radioactivity in irrigation at selected areas of Peninsular Malaysia - Khoirul Solehah Abdul Rahim,; Zalita Zainuddin,; Mohd Idzat Idris,; Priharti, Wahmisari; Sh. Aswood, Murtadha (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study involves a comprehensive analysis of 226Ra, 232Th, and 40K concentration from irrigation water samples. Water samples were obtained, and the physical parameters were examined. Subsequently, the corresponding radiological risks to human health were estimated. The concentration levels of 226Ra, 232Th, and 40K in water samples amounted to 1.51 ± 0.30, 0.17 ± 0.09, and 7.67 ± 3.07 Bq L-1, respectively, which were within the concentration levels reported in the literature from Malaysia and other countries worldwide. Based on the food intake rate by MoH and UNSCEAR, the annual ingestion effective dose (ID) and the cancer risks corresponding to radionuclide intake in irrigation were below the recommended maximum values. Meanwhile, the average hazard indices and annual outdoor effective dose (ED) amounted to 0.01 and 1.39 mSv year-1, respectively. It was inferred from the findings of this study that the water used as the sample does not have any significant radiological impacts to human body and is safe to be used as irrigation in the related area.